Assessment of the application for renewal of authorisation of Levucell® SC (Saccharomyces cerevisiae CNCM I‐1077) as a feed additive for dairy ewes and dairy goats. (24th July 2018) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria De Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Levucell ® SC is the trade name for a feed additive based on viable cells of a strain Saccharomyces cerevisiae . The product is currently authorised for use in feed for horses, lambs, dairy sheep, dairy goats, dairy cows and cattle for fattening. This opinion concerns the renewal of the authorisation of Levucell ® SC as a zootechnical additive for dairy ewes and dairy goats. S. cerevisiae is considered by EFSA to be suitable for the Qualified Presumption of Safety (QPS) approach to establishing safety for the target species, consumers and the environment. The identity of the strain present in the additive was established. Accordingly, this strain is presumed safe for the target species, consumers of products from animals fed the additive and the environment. Since no concerns are expected from other components of the additive, Levucell ®  SC is considered safe for the target species, consumers of products from animals fed the additive and the environment. The applicant has provided data demonstrating that the additive currently in the market complies with the conditions of authorisation. Furthermore, according to the information provided in the technical dossier, no new evidence has been identified that would make the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) reconsider the previous conclusions on the safety of the product for target species, consumers and the environment under the authorised conditions of use.